Self-reported pediatricians' management of the well-appearing young child with fever without a source: first survey in an European country in the anti-pneumococcal vaccine era - Principi Nicola; Venturini Elisabetta; Bonsignori Francesca; Galli Luisa; Chiappini Elena; de Martino Maurizio (BMC, 2009)
Abstract Background Recent studies suggest a substantially reduced risk of invasive bacterial infection in children vaccinated with heptavalent pneumococcal conjugate vaccine (PCV). To investigate whether the introduction of PCV might affect clinical decision making, we conducted a cross-sectional survey aimed at Italian Pediatric physicians. Results The study included 348 (46.5%) primary care pediatricians; 251 (36.4%) hospital pediatricians, and 139 (20.1%) pediatric residents. In an hypothetical scenario, a well-appearing 12-month-old child with fever without source would be sent home with no therapy by 60.7% (419/690) of physicians if the child was not vaccinated with PCV. The proportion increased to 74.2% (512/690) if the child had received PCV (P < 0.0001). Also, physicians would obtain blood tests less frequently in the vaccinated than in unvaccinated children (139/690 [20.1%] vs. 205/690 [29.7%]; P < 0.0001), and started empiric antibiotic therapy less frequently (3.0% vs. 7.5%; P < 0.0001). In the hypothetical event that white blood cell count was 17,500/μL, a significantly lower proportion of physicians would ask for erythrocyte sedimentation rate (P < 0.017), C reactive protein (P < 0.0001), blood culture (P = 0.022), and urine analysis or dipstick (P = 0.028), if the child had received PCV. Only one third of participants routinely recommended PCV. Conclusion Our data suggest that implementation of educational programs regarding the proper management of the febrile child is needed.